ЛЕКСЕМАТА стрига/shtrig[ ВО МАКЕДОНСКИОТ И ВО АЛБАНСКИОТ ДИЈАЛЕКТЕН ЈАЗИК (Филолошки студии, 2019)
The article refers to the meaning of the word shtriga used in Macedonian and Albanian dialects spoken in Macedonia. This word also has an extended use in the other Balkan languages (Greek, Romanian South Slavic language) in their material spiritual and social cultures. Apart from the basic meaning of the lexeme shtriga it bears figurative and other semantic meanings.